Experimental Study and Application of LASC Foamed Concrete to Create Airtight Walls in Coal Mines - Duo Zhang; Weifeng Wang; Jun Deng; Hu Wen; Xiaowei Zhai (Advances in Materials Science and Engineering)
If an airtight wall in a coal mine leaks air, it may cause spontaneous combustion of residual coal in the gob and even cause a full-blown fire or gas explosion. In this study, we developed a new type of foamed concrete, low-alkalinity sulphoaluminate cement (LASC), to control air leakage. The performance of filling materials that were prepared by adding various dosages of foam to LASC was studied. The longer the curing period for the foam filling material of LASC, the better the crystallinity of the hydrated product. With an increasing foam dosage, the initial setting time gradually extends while the fluidity of the foam slurry decreases. The bubble rate of the filling material increases and the density decreases with increasing foam dosage. The compressive strength of the LASC filling material decreases with increasing foam dosage and increases with increasing curing time. In the LASC filling materials, the optimal volume ratio of foam dosage to gel slurry is 2. The crystallinity, initial gel time, and compressive strength of the LASC foaming materials are better than those of ordinary Portland cement (OPC) foaming materials. When the crossheading is filled with LASC foam cement, the deformation of the surrounding rock is less than 19 cm, and the air leakage prevention is better than that achieved with loess and fly-ash-cement foam. Thus, the proposed LASC foam material can be applied to the filling of the crossheading to efficiently prevent leakage in underground coal mines.